Combination of Diet Quality Score, Plasma Carotenoids, and Lipid Peroxidation to Monitor Oxidative Stress. (31st December 2018) - Kim, Yunsoo; Kim, You Jin; Lim, Yeni; Oh, Bumjo; Kim, Ji Yeon; Bouwman, Jildau; Kwon, Oran
Abstract : It is important to understand the association between oxidative stress-related parameters and to evaluate their status in advance of chronic disease development. Further development towards disease can then be prevented by dietary antioxidants. The present study was aimed at assessing the relationship between diet quality, blood antioxidants, and oxidative damage to determine whether the association between these markers differs by oxidative stress status. For a cross-sectional analysis, we used data and samples of baseline information from a prospective cohort study. A total of 1229 eligible adults were classified into apparently healthy subjects (66.5%) and those with oxidative stress conditions (35.5%). Diet quality was assessed using the recommended food score (RFS). Plasma carotenoids (blood antioxidants) and blood/urinary malondialdehyde (MDA; oxidative damage) were determined by high-performance liquid chromatography. We found that the healthy group was younger, and they had a lower RFS and plasma MDA level and higher plasma carotenoids compared to the oxidative stress condition group. This result is probably due to the quenching of the oxidative response in the tissues of those people. A positive association of RFS with plasma carotenoids (total and β -carotene) was found in both groups, suggesting that carotenoids are a robust reflection of diet quality. Negative associations were observed between plasma MDA and RFS in the oxidative stress condition group and between urinary MDA and plasma zeaxanthin in the healthy group. Erythrocyte MDA was positively associated with plasma carotenoids (total, lutein, zeaxanthin, β -cryptoxanthin, and α - and β -carotene), regardless of health condition, probably also as a result of the use of carotenoids as antioxidants. In conclusion, these results indicate that the above three factors may be associated with the oxidative stress response and depend on the oxidative status. Furthermore, it was also suggested that erythrocytes are important in the oxidative stress response and the quenching of this response is represented in plasma carotenoids.